Development of digital and science, technology, engineering, and mathematics skills in chemistry teacher training - Elías, Michal; Pérez, Javiera; Cassot, Montserrat del Rosario; Carrasco, Eduardo Andrés; Tomljenovic, Marijana; Zúñiga, Elisa Ariadne (Frontiers in Education, 2022)
This work reviews the concepts associated with digital and STEM skills. Through a case study, the perception of the students in the development of these competencies and the commitments assumed in the study plans during the initial formation of Professor of Chemistry in a Chilean state university are analyzed. A mixed type of investigation was performed, considering three phases with different methodologies. The first phase consisted of a bibliographic study comparing both the digital and STEM skills of several organisms referents for Chilean education (UNESCO, MINEDUC and ISTE). A second phase refers to the analysis of the study plan programs associated with STEM, ICT, and chemistry teaching, through an Analysis Matrix of Aprioristic Categories. In a third phase, the perceptions of development digital skills of Chemistry Professors undergraduate students were evaluated through the Digital Competence Questionnaire of Higher Education Students. The analysis of the study programs shows that students' digital skills are far from the ones required by the Chilean Ministry of Education (MINEDUC). But they enhance more complex cognitive levels when the curricula advance, promoting STEM skills. The CDAES survey shows a development proportional to the curricular pursuit of the students where, in the first year of the degree, the students declare positive answers in 60.5% of the items consulted. This trend increases in the second and third years (90.7% of positive answers) and in the fourth and fifth years (93.0% and 95.4% of positive answers). It remains a challenge to develop skills to design, create or modify technological educational media that promote the use of digital and STEM skills. In conclusion, the teacher training curriculum does not have an explicit association with digital and STEM skills, although it addresses the skills required by national and international benchmarks. However, the students declared a positive attitude towards digital skills developed progressively during their training as teachers. As future Chemistry Teachers, they value the development of digital teaching skills that allow them to address the challenges that arise in the classroom and thus promote the appreciation of STEM careers, which helps form citizens who will walk towards sustainability.